2020
DOI: 10.1107/s1600576720010687
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening of in cellulo grown protein crystals via a small-angle X-ray scattering/X-ray powder diffraction synergistic approach

Abstract: Crystallization of recombinant proteins in living cells is an exciting new approach for structural biology that provides an alternative to the time-consuming optimization of protein purification and extensive crystal screening steps. Exploiting the potential of this approach requires a more detailed understanding of the cellular processes involved and versatile screening strategies for crystals in a cell culture. Particularly if the target protein forms crystalline structures of unknown morphology only in a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…Applying the parameters of a primitive hexagonal unit cell, 5520 of the recorded detector images were successfully indexed (a 27% indexing rate). The refined unit-cell parameters are comparable to those extracted from previous X-ray diffraction experiments (Yuan et al, 2003;Lahey-Rudolph et al, 2020, confirming the indicated similar composition of the in vitro-grown and in cellulo-grown HEX-1 crystals. The structural model of HEX-1 refined at 2.30 Å resolution is superimposable on that obtained from FT-SFX of in cellulo-grown HEX-1 (Lahey-Rudolph et al, 2021), with an overall r.m.s.d.…”
Section: Establishing Hare Chips For In Cellulo Synchrotronsupporting
confidence: 82%
See 3 more Smart Citations
“…Applying the parameters of a primitive hexagonal unit cell, 5520 of the recorded detector images were successfully indexed (a 27% indexing rate). The refined unit-cell parameters are comparable to those extracted from previous X-ray diffraction experiments (Yuan et al, 2003;Lahey-Rudolph et al, 2020, confirming the indicated similar composition of the in vitro-grown and in cellulo-grown HEX-1 crystals. The structural model of HEX-1 refined at 2.30 Å resolution is superimposable on that obtained from FT-SFX of in cellulo-grown HEX-1 (Lahey-Rudolph et al, 2021), with an overall r.m.s.d.…”
Section: Establishing Hare Chips For In Cellulo Synchrotronsupporting
confidence: 82%
“…Its spontaneous self-assembly into intracellular crystals also occurs in insect cells after infection by a recombinant baculovirus (rBV) encoding the HEX-1 gene. Regular, micrometresized hexagonal crystals grow reproducibly and with high efficiency in living insect cells (Lahey-Rudolph et al, 2020). In the High Five insect cells used here, crystal growth is observed 48 h after rBV infection at the earliest, with a maximum of crystal-containing cells 96 h after infection.…”
Section: Intracellular Protein Crystallizationmentioning
confidence: 83%
See 2 more Smart Citations
“…We recently reported that spontaneous self-assembly of HEX-1 into intracellular crystals is not restricted to the native environment of the fungal cells. On infection with a recombinant baculovirus encoding the HEX-1 gene, living insect cells also form regular, micrometre-sized hexagonal crystals (Lahey-Rudolph et al, 2020), supporting a strong intrinsic crystallization tendency of HEX-1 that might have evolved along with its physiological function.…”
Section: Introductionmentioning
confidence: 85%